2017
DOI: 10.1016/j.jphotochem.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Innovative and stable TiO 2 supported catalytic surfaces removing aldehydes under UV-light irradiation

Abstract: The present study reports the photocatalytic degradation of aldehydes using TiO 2 impregnated polyester (PES) and glass fiber (GFT)-TiO 2 addressing the photocatalytic degradation aldehydes (air-solid interface). The PES-TiO 2 optical absorption was determined by diffuse reflectance spectroscopy (DRS). By X-ray diffraction (XRD), the formation of TiO 2 anatase on the PES surface was detected. The photocatalytic oxidation (PCO) of butyraldehyde and isovaleraldehyde was carried out in a batch photo-reactor equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The reactors used for water treatment by photocatalysis can be classified into two main configurations: reactors with suspended photocatalytic particles and reactors with immobilized photocatalyst. Systems based on the use of suspended catalyst were preferred due to their large active surface area per unit volume and the ease of regenerating once used with a simple wash with deionized water [12,21,50]. The configuration supported does not require a downstream separation stage either by decanting tanks or a cross-flow filtration system, to allow the reactor to operate continuously, but requires maintenance processes for reuse the catalyst after each use as a result of fouling [19].…”
Section: Photocatalytic Reactor Configurationmentioning
confidence: 99%
See 3 more Smart Citations
“…The reactors used for water treatment by photocatalysis can be classified into two main configurations: reactors with suspended photocatalytic particles and reactors with immobilized photocatalyst. Systems based on the use of suspended catalyst were preferred due to their large active surface area per unit volume and the ease of regenerating once used with a simple wash with deionized water [12,21,50]. The configuration supported does not require a downstream separation stage either by decanting tanks or a cross-flow filtration system, to allow the reactor to operate continuously, but requires maintenance processes for reuse the catalyst after each use as a result of fouling [19].…”
Section: Photocatalytic Reactor Configurationmentioning
confidence: 99%
“…Regarding the recovery of TiO 2 particles, using a concentration of 100.0 mg L −1 , instead of 2.0-3.0 g L −1 dosage used by Bansal et al [18], would considerably facilitate their separation by means of a tangential membrane filtration. Operating costs would not increase because of the improvement in degradation yields of approximately 25%, since there is no need of having to resort to a highly complex supported configuration using pebbles, glass spheres or silica gel beads [12,[19][20][21][22].…”
Section: Photocatalytic Reactor Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…BET, SEM, and other tests showed that the specific surface area of the TiO 2 (40%)@CdS composite was the largest. TiO 2 nanorods and CdS particles were uniformly distributed in the composite, and the optical response range was extended to the visible light region.Catalysts 2020, 10, 441 2 of 14 coating, the nitric oxide (NO x ) in the atmosphere [8,9], sulfur oxide [10,11] and other pollutants such as halogenated hydrocarbons [12,13], aldehydes [14], and polycyclic aromatic hydrocarbons from automotive exhaust gas can be absorbed and degraded [15,16]. TiO 2 also shows a good performance in light-sensitive solar cells [17] and biomedical devices [18].…”
mentioning
confidence: 99%